Convergence of economic growth and digitalization of households: spatial analysis of interrelation with regional panel data - E. I. Kadochnikova (Russian Journal of Economics and Law)
Objective: to assess the relationship between the digital infrastructure of households and the average rate of economic growth in the regions, taking into account short- and long-term spatial dependencies.Methods: global Moran and Geary spatial correlation indices, local Moran spatial correlation index, econometric model with spatial autoregression lag, econometric model with spatial interaction in errors, maximum likelihood method.Results: a positive spatial relationship for the gross regional product per capita and the share of the population using the Internet was shown; the positive influence of neighboring regions on economic growth in the given region was confirmed; local spatial clusters of regions by the share of the population using the Internet were found; conditional β-convergence of the average growth rates of the gross regional product both short- and long-term was revealed; Solow’s conclusion about the decreasing return of the excess factor of production was confirmed; a positive impact was found of the number of active subscribers of mobile broadband access to the Internet per 100 inhabitants on the average growth rate of gross regional product, on the share of households having personal computer, on the proportion of households having access to the Internet, and on the average growth rate of gross regional product.Scientific novelty: for the first time, the article uses Russian regional panel data for the period from 2014 to 2017 to measure the relationship between the digital infrastructure of households and the average rate of economic growth, taking into account spatial dependencies.Practical significance: the main conclusions of the article can be used in scientific and practical activities to develop measures to increase the rate of regional economic growth by stimulating investment and consumer demand of households.